Mimi - Baicker-McKee, Carol, 1958- (Bloomsbury Children's Books : Distributed to the trade by Macmillan, 2008)
Mimi the pig and her bunny spend a very busy day at the library, the park, and home, but all the while she is thinking of her pet roly-poly bug, Frank, who has been missing since breakfast.